Does Air Pollution Cause the Retail Investor’s Disposition Effect in Taiwan Mutual Fund Markets? - Ko, Jim-Chen; Chang, Fu-Min; Chen, Yu-Hao; Lin, Yih-Bey; Lee, Nicholas (International Journal of Energy Economics and Policy, 2019)
Disposition effect is a biased behavior of investor, which sells winners too early and rides losers too long. Retail investors may have a disposition effect compared to professional investor because retail investors may lack of expertise or their psychology are affected easily by external factors, such as weather, temperature, mood, etc. Recently, Taiwan suffers from air pollution problem. Does air pollution cause the retail investor’s disposition effect? By using multiple regression analysis, this article investigates the relationship between air pollution and retail investor’s disposition effect in Taiwan mutual fund market. We divide the market conditions into three states, bull, bear, and neutral. Empirical results revealed that although there is no significant correlation between air pollution and the disposition effect in the overall Taiwan mutual fund market, but the retailer investor’s behavior is more conservative as the degree of air pollution increases under the bull and bear markets. Keywords: Mutual Fund, Disposition Effect, Air Pollution, Multiple Regression Analysis JEL Classifications: E22, G40, Q53 DOI: https://doi.org/10.32479/ijeep.7299